2009
DOI: 10.1007/s00103-009-0961-y
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine safety

Abstract: Vaccinations rank among the most effective preventive measures for protection against infectious diseases. Advances in development, production, and control of vaccines facilitate the increasing standards of vaccine safety and tolerance. Comprehensive pre-clinical and clinical tests as well as modern manufacturing and testing methods ensure that vaccines marketed nowadays are safe. As a rule, clinical trials performed before granting the marketing authorisation identify the most frequent adverse events and thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 59 publications
0
27
0
4
Order By: Relevance
“…Likewise, the journal retracted the publication and Wakefield was barred from practicing medicine (148)(149)(150). Numerous other studies found no significant association between the MMR vaccine or the mumps virus and autism spectrum disorder (ASD) (72,81,(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163)(164). A recent nationwide cohort study in Denmark by Hviid et al (164) used the Danish population registries to evaluate whether the MMR vaccine increased the risk for autism in children, subgroups of children or time periods after vaccination.…”
Section: Vaccines Cause Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the journal retracted the publication and Wakefield was barred from practicing medicine (148)(149)(150). Numerous other studies found no significant association between the MMR vaccine or the mumps virus and autism spectrum disorder (ASD) (72,81,(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163)(164). A recent nationwide cohort study in Denmark by Hviid et al (164) used the Danish population registries to evaluate whether the MMR vaccine increased the risk for autism in children, subgroups of children or time periods after vaccination.…”
Section: Vaccines Cause Autismmentioning
confidence: 99%
“…The threshold level for formaldehyde in vaccines is 0.02 % (0.2 g/L) ( 81 , 82 ). Additionally, nowadays the formaldehyde-based inactivation is followed by its removal.…”
Section: Formaldehydementioning
confidence: 99%
“…Other hypothetical side effects of vaccination have almost been ruled out, such as multiple sclerosis, diabetes mellitus type 1, or autism [4649]. …”
Section: Principles Of Vaccination In Elite Athletesmentioning
confidence: 99%
“…Impfungen verursachen keine Epilepsie [7], jedoch können im Rahmen von mit Impfungen assoziiertem Fieber bei entsprechender genetischer Disposition Fieberkrämpfe auftreten. Eine retrospektive Analyse von Berkovic et al [8] konnte bei 11 von 14 Patienten mit der Diagnose einer vermeintlichen "chronischen postvakzinalen epileptischen Enzephalopathie" nachweisen, dass die Symptomatik nicht [11]. HHE wurden nach Verabreichung zahlreicher Impfstoffe, am häufigsten nach den früher verwendeten Pertussisganzkeim-Kombinationsimpfstoffen beschrieben.…”
Section: Bekannte Neurologische Symptome Nach Impfungenunclassified
“…Hypoton-hyporesponsive Episoden (HHE) sind kollapsähnliche Reaktionen bei Säuglingen und Kleinkindern, die durch plötzliches Auftreten einer erniedrigten Muskelspannung (hypoton), reduzierte Ansprechbarkeit und Reaktion auf Reize (hyporesponsiv) und bläuliche Hautfärbung oder Blässe charakterisiert sind. Die mittlere Zeit zwischen Impfung und Auftreten der Symptomatik liegt bei 3–4 h (Zeitspanne: wenige Minuten bis 48 h), die Dauer beträgt zwischen 6 und 30 min (bis zu einigen Tagen) [ 11 ]. HHE wurden nach Verabreichung zahlreicher Impfstoffe, am häufigsten nach den früher verwendeten Pertussisganzkeim-Kombinationsimpfstoffen beschrieben.…”
Section: Bekannte Neurologische Symptome Nach Impfungenunclassified